The effect of heat input on defect formation, macrostructure, microstructure and hardness in AA 1100 aluminum weld joints using the GMAW process - Rizki Dwi Ardika; Ilham Sulthoni; Munaji Munaji; Yoyok Winardi; Muizuddin Azka (Jurnal Polimesin, 2026)
AA 1100 aluminum is widely used in industrial applications due to its low density and good corrosion resistance; however, welding defects such as porosity and changes in mechanical properties often occur during Gas Metal Arc Welding (GMAW). One of the most influential parameters on weld quality is the welding current. This study analyzes the effect of welding current variations on the physical and mechanical properties of AA 1100 GMAW welded joints using ER 5356 filler wire. Welding was carried out at currents of 100 A, 130 A, and 160 A using argon shielding gas. The welded joints were evaluated by visual inspection, macrostructure observation, microstructure analysis, and Vickers microhardness testing. The test results showed that increasing the welding current resulted in wider weld beads, increased porosity and spatter defects, as well as coarser grain structures in the heat-affected zone (HAZ) and weld metal. The lowest porosity and spatter occurred at 100 A, while the highest porosity and spatter occurred at 160 A. This was due to excessive heat input and hydrogen trapping. Microstructural analysis revealed the presence of FeAl₃ intermetallic phases dispersed within the aluminum matrix. The highest hardness value was found in the weld metal region at 100 A, which was caused by the finer grain size and the strengthening effect of Mg from the ER 5356 filler. Overall, this study confirmed that the welding current significantly affects the defect formation, microstructural evolution, and hardness distribution of GMAW AA 1100 weld joints.